Revolutionizing Mountainous Countries’ Transportation: CASWAT-G Surface Ropeway for Multifaced Application - Baral, Lok B.; Nalmpantis, Dimitrios; Amatya, Vishwa P.; Sah, Chandan K. (Amrit Research Journal, 2023)
Mountainous regions often present formidable barrier to traditional transportation system, limiting access and impending economic growth. In this regard, a new technology called CASWAT-G (Circulating Cable Supported Up-down Walking Technology by Using Gravity) surface ropeway (CSR) is one that uses simple parts and eases up-down walking because of the harvested gravitational potential energy (GPE) from the descending user. Different prototype test result showed the efficiency of the CSR’s machine is above 80%. Technically verified CSR is very much useful to use for transportation to support people living in the hilly region and for the tourism trade. This technology is very simple, low cost, eco-friendly, sustainable and can be set up quickly with minimum environment impact. Its multi faced application can be in the different fields like: public transport, tree climbing, fun and learning for children, carrying goods, and tourism. Based on the Ph.D. thesis and previous papers of mine, the possible application of the work is described in this paper and it contains graphs, calculations, etc. of previous work.